PENGARUH ASAM GIBERELAT (GA3) DAN KALIUM NITRAT (KNO3) SERTA INTERAKSINYA TERHADAP SENESCENCE BUNGA POTONG GERBERA PUTIH (Gerbera jamesonii). - Maulidina Agustin; Martha Lulus Lande; Zulkifli Zulkifli; Tundjung Tripeni Handayani (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2019)
The purpose of this study was to decide whether the mixture of KNO3 and GA3 solutions was more effective than a single solution of KNO3 or GA3 in maintaining the freshness of cut flowers. The study was conducted at the Botanical Laboratory of the Department of Biology, Faculty of Mathematics and Natural Sciences, University of Lampung from November - December 2017. The research was carried out in a 2 x 3 factorial experiment with reason A was the GA3 solution with 3 concentration levels: 0%, 0.5%, and 1%. Factor B is KNO3 solution with 2 concentration levels: 0% and 5%. The limits in this study were fresh weight, dry weight, relative water content, and total dissolved carbohydrate content of gerbera cut flowers, qualitative limits were the level of reducing sugars. Measurements were made 7 days after soaking cut flowers in KNO3 or GA3 solutions, and a mixture of both. Homogeneity of variance and analysis of variance were determined at a significant level of 5%. Simple effect of KNO3 at each concentration level of GA3 decide by F test at 5% significance level. The results showed that GA3 with a concentration of 0.25% and 0.5% increased the fresh weight and dry weight of Gerbera cut flowers. KNO3 0.5% much reduced the relative water content of Gerbera cut flowers. The interaction between GA3 and KNO3 does not much effect all freshness of cut flowers. From the results of the study concluded that the single treatment of GA3 was more effective than the combination treatment of GA3 and KNO3 in maintaining the freshness of Gerbera cut flowers.